Dismantling the National Health Service in England. (October 2022) - Roderick, Peter; Pollock, Allyson M.
The National Health Service was established in the United Kingdom in 1948 as a universal, comprehensive service free at the point of delivery, which is publicly provided, funded, and accountable. Market incrementalism in England has eroded this system over three decades. The recently enacted Health and Care Act will erode it further. This article first explains briefly how legislation and policy initiatives in 1990, 2003, and 2012 furthered development of the market and private provision of health services, and then describes the main structural changes in the new Act and their implications. England is now moving decisively toward a marketized, two-tier, mixed-funding system with several similarities to the United States.